Improving marketing performance through business agility and market orientation in micro, small, and medium enterprises in Semarang City - Sri Suprapti; Suparmi Suparmi (Arthatama: Journal of Business Management and Accounting, 2022)
Environmental conditions are very uncertain due to the Corona Virus -19 (Covid-19) pandemic coupled with the very tight business competition; business Agility (business agility) is a very important key for companies to maintain their performance. Understanding and practicing business agility that leads to success is very important for business people. This study investigates the impact of business Agility and market orientation related to competitive advantage and marketing performance in Micro, Small, and Medium Enterprises (MSMEs) in Semarang City. The population of this research is all MSMEs in the city of Semarang, amounting to 17,564. The sample of this study amounted to 100 MSMEs using the Solving formula and proportional sampling technique. The data collected from 100 MSMEs in Semarang City are categorized into five types of businesses: Food MSMEs, Convection MSMEs, Trade MSMEs, Services MSMEs, and Animal Husbandry MSMEs. The analysis reveals that business agility and market orientation significantly improve competitive advantage and marketing performance. Competitive advantage can mediate business agility and market orientation towards marketing performance. This finding confirms that business agility creates a tendency for MSMEs owners always to have access to market changes and learn in business development to achieve competitive advantage and marketing performance. The implications of this finding emphasize that external environmental factors that cause risk tendencies will encourage MSMEs owners always to pay attention to environmental changes and always make efforts to adapt quickly, precisely, and flexibly to the dynamics that occur in the market, therefore MSMEs need to take advantage of the company’s knowledge and resources to maintain its business and improve its competence excellence and company performance.